A study on the factors that affecting the volatility of natural rubber price in Malaysia / Mohd Zulfadli Zulkefle - Zulkefle, Mohd Zulfadli (2014)
This paper will investigate the determinant that make natural rubber price volatile, first of all, Malaysia is the third largest producer of natural rubber after Thailand and Indonesia. In this research paper the researcher will determine factors that will affect volatility in natural rubber price may be a result of international trade, crude oil price and synthetic rubber production. The data used for this study is from January 2001 – August 2013 every monthly that obtained from Malaysia department of statistic and data stream. Therefore an Eviews model has been applied for this paper to test the hypothesis and identify the relationship between the variables. The test that researcher do for this research are unit root test, descriptive analysis, correlogram analysis and regression model. Whereby, the dependent variables for this study are natural rubber price in Malaysia, while the independent variables for this study are crude oil price, natural rubber export, natural rubber import and synthetic rubber production. Based on previous research studies, import variables have negative relationship with the rubber price in Malaysia to indicate this result researcher will make research whether from the previous study the researcher will get the same result or vice versa. Otherwise for the result shows that crude oil price has positive relationship with volatility natural rubber price in Malaysia. The major implication of the finding is dependence on one commodity as a source of export earning is subject to risk, in another words the diversification of export crop promotion must be continued